Expression of matrix metalloproteinase-13 in human skin melanoma cancer treated by baccaurea angulata in vitro - Abdull Rasad, Mohammad Syaiful Bahari (2013)
Currently, B. angulata has not been fully exploited as little is known regarding the scientific and anti-cancer properties of the fruit. Also, the degree of Matrix Metalloproteinase-13(MMP-13) association in the development and metastasis of cancer remains to be scantily known